Aeropuerto: disenchantment, dialectical rescue. Issue 4 (2nd October 2019) - Aparicio, Tania
ABSTRACT: At the intersection of the critical and the creative, my contribution builds on my work in visual-ethnography. I have been recording video at the site of a 'future' international airport in rural Peru. I call the project Aeropuerto . Aeropuerto is a visual archive of objects and places in transition. It's a collection of images about the arrival of an international airport and the economic development it promises – a seemingly linear process that is happening very fast in a Quechua community that, until recently, experienced time cyclically. Now, I engage with Aeropuerto to convolute images and theoretically informed ideas. For this exploration, I play with my visual ethnography as an expression of the dialectical image. I present how a 'future' airport is materialising in constructed environments, landscapes and other forms of cultural expression to question the linearity of the process of development and the losses and erasures it brings. I slow down the fast pace of linear temporality and challenge its rapidity with a ludic application of the 'now time', illustrating a visual story in which the world of things awaits the dialectical rescue we see with Benjamin's theory of collection. This project is comprised of written and video components.